Hernioplasty in One-Day Surgery: result of 228 self-adhesive prosthesis - Goulart, A (2013)
Aim: To evaluate the outcomes of inguinal hernia repair with ProGrip® mesh in same-day surgery Methods: Follow-up data was collected at 24 hours and 30 days after surgery. Results: In one year, 228 patients underwent surgical repair of unilateral inguinal hernia. At 24 hours after surgery, 50.64% of patients reported some degree of pain and 66.3% were able to move around the house with few limitations. Thirty days after surgery, 94.39% of patients had returned to their routine activities. Conclusions: The use of the ProGrip® mesh is associated with low post-operative pain and rapid recovery.